Limits of the legal regulation of the state programs financing: features of definition and properties - Пашинська, Вікторія Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The author examines types of the regulatory boundaries, contributing to the formation of external and internal areas of financial and legal regulation of state programs financing. Also in the paper the author formulates properties of the limits of the legal regulation of state programs financing. The development of social relations in modern Ukraine requires timely and adequate adaptation of the national legislation and the whole mechanism of regulation. At the same time, from a practical (especially law-making) perspective, the legal influence as a way of government regulation needs to outline the extent of its effect on certain relationships. Particular relevance in this context is constituted of legal relation of the financing of state programs, which are related to basic tactical and strategic objectives of the country and society.